Determination of Uranium in Aqueous Solutions by Means of Gamma Absorptiometry - Cristallini, Osvaldo A.; Gantner, E.; Von Baeckmann, A. (Institut für Radiochemie; Alemania, 1972)
Fil: Cristallini. Osvaldo A. Comisión Nacional de Energía Atómica; Argentina